2022
DOI: 10.1186/s12872-022-02844-x
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and health-related quality of life of inpatients with coronary heart disease: a cross-sectional study in Lanzhou city, China

Abstract: Background A key outcome in coronary heart disease (CHD) is Health Related Quality of Life (HRQoL), and family functioning is important in the management of CHD. But few studies have examined both together, and little is known about them among inpatients with CHD in less developed areas of China. Therefore, this study aimed to assess the HRQoL and family functioning status of inpatients with CHD in Lanzhou from Northwest China, and identify the factors that affect their HRQoL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
11
2
2
Order By: Relevance
“…Interestingly, the present study found that the educational level of gout patients did have a signi cant impact on the GIS dimension of unmet gout treatment need (β = 1.795). This nding is not in agreement with some other studies [21,22] . A possible reason for this is that people with high educational levels may have access to better health-related knowledge and skills [23,24] , while information may have a negative impact on healthcare utilization [25] .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the present study found that the educational level of gout patients did have a signi cant impact on the GIS dimension of unmet gout treatment need (β = 1.795). This nding is not in agreement with some other studies [21,22] . A possible reason for this is that people with high educational levels may have access to better health-related knowledge and skills [23,24] , while information may have a negative impact on healthcare utilization [25] .…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have not found that education level is associated with HRQoL in gout patients, although it clearly does in other chronic diseases [21,22] . Interestingly, the present study found that the educational level of gout patients did have a signi cant impact on the GIS dimension of unmet gout treatment need (β = 1.795).…”
Section: Discussionmentioning
confidence: 81%
“…Проаналізувавши ПКЗ, зазначимо, що відсутність значущих розбіжностей показників РЕФ, СФ, ЖЗ і ПЗ (р > 0,05) вказує на низький вплив психічної складової ЯЖ залежно від віку пацієнта. Доведено, що особи похилого віку мають достовірно нижчу ЯЖ [4]. Імовірно, це зумовлено соціальною складовою, рівнем доходу чи навіть місцем проживання.…”
Section: обговоренняunclassified
“…Зазначимо, що реваскуляризація зменшує прояви СтСт, запобігає розвитку коронарних інцидентів, але зниження фізичної активності та ЯЖ залишаються проблемою навіть після оптимальної реваскуляризації, і це також є економічним тягарем для сфери охорони здоров'я [4].…”
unclassified
“…Previous studies have identified biological, psychological and social factors that influence HRQOL in the Chinese population, such as disease (Tian et al., 2021), social support (Burnette et al., 2021) and public health services (Lai et al., 2021). Notably, HRQOL is affected by many family‐related factors, including the family's income (Ha et al., 2022), communication (Lim & Shon, 2018), relationships (Zhang et al., 2021), structure (Liu et al., 2015), lifestyle (Chen et al., 2020) and functioning (Zhang, Wang, et al., 2022). Family health is defined as a resource at the level of the family unit that develops from the intersection of the health of each family member, their interactions and capacities, as well as the family's physical, social, emotional, economic and medical resources (Weiss‐Laxer et al., 2020).…”
Section: Introductionmentioning
confidence: 99%